Linking Transformational Leadership to OCB in Hospitality Industry: the Mediating Influence of Affective Commitment and Work Engagement - Istiqomah, Suryandari; Riani, Asri Laksmi (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2021)
This paper aims to examine the process of Organizational Citizenship Behavior (OCB) employee in hospitality industry especially in hotel and restaurant. The author test the role of transformational leadership and mediation role of affective commitment and work engagement toward OCB in workplace. Data were colleted from 218 hospitality employees in frontliner area.Ã‚Â Instrument convergen and discriminant validity and hypothesize test using structural equation model - partial least square (SEM-PLS) method with SMART PLS 3. Ã‚Â The result show that transformational leadership have positive effect toward OCB. In addition,Ã‚Â affective commitment and work engagement also show partial mediation effect in relationship between transformational leadership and OCB in workplace. The results showed that transformational leadership has no direct effect on OCB like most other Asian studies. This study found that transformational leadership can influence OCB through the mediating effect of affective commitment and work engagement. These results are expected to enrich the psychological mechanisms that can explain the effect of transformaional leadership on OCB. Future research is expected to be able to explain a more comprehensive flow of transformational leadership, affective commitment, work engagement and OCB.